Numerical modeling of forming air impact thermoforming - Wagner, Simon; Kayatz, Fabian; Münsch, Manuel; Sanjon, Cedric W.; Hauptmann, Marek; Delgado, Antonio (International Journal of Advanced Manufacturing Technology, 2022)
Thermoforming is a complex process with numerous parameters that potentially have an influence on the wall thickness distribution of the end product. Test benches do not allow for measuring all potentially relevant influences. Numerical simulations therefore have proven to be a useful tool in order to obtain deeper insight into the process and the mutual interactions between the input parameters. Forming air impact thermoforming can be thought of as an extension to common negative thermoforming that takes advantage of the flow inside the pressure chamber to obtain a favorable deformation behavior, ultimately leading to an improved final wall thickness distribution. The purposeful interaction between flow field and plastic sheet implies a significantly more complex physical system when approaching the process with modeling techniques. This paper describes the setup of a structural simulation model for thermoforming, that in an approximative manner includes effects of the flow field within the pressure box on the deforming plastic sheet. Special focus is laid on the implementation of counter-pressure due to the air trapped between sheet and mold. Validation simulations presented yield satisfactory results and thus show the high potential of simulations in modeling the complex interactions occurring in forming air impact thermoforming.
CRIS-Team WoS Importer:2022-04-08